ANALISIS LITERATUR TENTANG PERBEDAAN ONE-WAY, TWO-WAY, DAN MULTIVARIATE ANALYSIS OF VARIANCE (MANOVA) - Harahap, Asrial Habiby; Khofifah Choirun Nisya Siregar; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the differences between three types of Analysis of Variance (ANOVA), namely One-Way ANOVA, Two-Way ANOVA, and Multivariate Analysis of Variance (MANOVA) in research. The method in this study is a literature study by analyzing scientific sources relevant to the topic of study. The results of the analysis show that the fundamental difference between the three analyses lies in the number of independent variables and dependent variables used. One-Way ANOVA is applied to analyze the effect of one independent variable on one dependent variable. Two-Way ANOVA is used to test the effect of two independent variables on one dependent variable, including the possibility of interaction between independent variables. Meanwhile, MANOVA is used in research involving more than one dependent variable that is analyzed simultaneously based on one or more independent variables